Programowanie języka dziecka z uszkodzeniem słuchu z zastosowaniem metody audytywno-werbalnej. Studium przypadku - Lorenc, Anita (Logopedia Silesiana, 2015)
The aim of this article is to present the problems of diagnosis, and the possibilities of language programming of a child with profound hearing loss using the auditory-verbal method. Therapeutic procedure refers to the proper development of the child’s speech.